The Role of China's Exchange Rate on the Trade Balance of Sub-Saharan Africa: a Gravity Model Approach - Hameed Khan; Umair Khan; Li Jun Jiang; Muhammad Asif Khan; Syed Hasanat Shah (Comparative Economic Research. Central and Eastern Europe, 2019)
This study seeks to investigate theimpactof China'sexchange rate onthe trade balance of 41 Sub-Saharan African countries for the period from 1994 to 2016. Using an augmented gravity model, the grouped and ungrouped results of the study confirm the elasticity and absorption approaches of the trade balance. Similarly, the robustness check, by dividing the sample period into two sub-periods (2005-2016 and 1994-2004), also confirms the elasticity and absorption approaches of the trade balance.
Keywords: F41; C23; 330; bilateral trade; China; SSA